Information Literacy Education of Higher Education in Asian Countries - Chen, Chao-Chen; Wang, Mei-Ling; Chu, Samuel Kai Wah; Ishita, Emi; Tuamsuk, Kulthida; Shamila, Mohamed Shuhidan (Learning Sciences for Higher Education, 2023)
V, 153 p. 21 illus., 19 illus. in color.